Synergizing Safe Behaviour, Safety Leadership, and Safety Communication: A Sociological Analysis of Safety Culture Formation and Operational Excellence in High-Risk Industries - Arief Zulkarnain; Puji Lestari; Kholil Kholil (Universitas Pattimura, 2026)
This study investigates the sociological dynamics shaping the formation of safety culture and its role in achieving operational excellence within high-risk industries. Despite widespread adoption of safety policies, organizations in Indonesia’s oleochemical sector remain limited by compliance-based practices that neglect the social, cultural, and communicative dimensions of workplace safety. Adopting a post-positivist paradigm and a sequential explanatory mixed-methods design, the research integrates quantitative analysis using Structural Equation Modeling (SEM-Lisrel) of 421 employee responses with qualitative thematic analysis through MAXQDA. The results reveal that safe behaviour, safety leadership, and safety communication jointly explain 87.2% of the variance in safety culture and 91.3% in operational excellence, with safety communication emerging as the strongest determinant linking policy to practice. Qualitative findings highlight safety as a socially constructed system grounded in trust, dialogue, and shared meaning, reinforced through practices such as Gemba Walks, Safety Talks, and Toolbox Meetings. The study’s novelty lies in its integrative sociological framework that unites behavioural, leadership, and communication dimensions of safety culture, traditionally treated separately, within a social systems perspective. Theoretically, it advances organizational and industrial sociology by conceptualizing safety culture as a dynamic interplay of structure, agency, and communication, offering both analytical depth and practical insight for sustainable safety management.